Sosialisasi Silaturahmi Pada Acara Halal Bi Halal - Puput Mulyono; Muhamad Habib (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service journal article discusses the practice of silaturahmi (social bonding) and the tradition of halal bi halal within Javanese society as part of the Eid al-Fitr celebration. These traditions represent a unique form of integration between Islamic values and longstanding local customs. Using Robert Redfield's theoretical framework of great tradition and little tradition, this article highlights how Islam, as a great tradition, did not replace local cultures, but instead blended harmoniously with the little traditions of the Javanese people. Eid al-Fitr in Java is celebrated with an atmosphere of joy, festivity, and togetherness—often perceived as more vibrant than in Islam’s place of origin. This distinctiveness stems from the culturally sensitive approach of early Islamic scholars and missionaries in Java, who avoided imposing radical changes on local traditions. Instead, they subtly and wisely revived ancient customs by integrating them with Islamic teachings. One notable outcome of this approach is the tradition of halal bi halal, a social innovation that has become a key cultural institution during Eid. It strengthens social bonds, reconnects families and communities, and serves as a medium for reconciliation. Through this lens, the article illustrates how the cultural and religious fusion can foster harmony and enrich religious practices without losing local identity. These findings offer meaningful insights for promoting tolerance and inclusivity in a pluralistic society.